Procesos biotecnológicos para determinar el efecto de las auxinas y citoquininas, en la inducción de estructuras organogénicas de Cinchona officinalis L., a partir de formaciones callogénicas - Correa Jaramillo, Jimmy Vicente (2024)
As a forest species of high economic, ecological, and medicinal significance, Cinchona officinalis L. is distributed in the mountain forests of the Andes and stands out in the southern region of the country as a native species. C. officinalis populations have been threatened by various anthropogenic activities and problems with their natural environment. Therefore, it is of vital importance to implement the use of alternative techniques, such as plant micropropagation, in order to conserve and increase C. officinalis individuals. In the present study, the goal was to determine the optimal hormonal balance for the differentiation of de novo organogenic structures from callogenic formations in Cinchona officinalis L. ; testing in Murashige and Skoog's culture medium, different combinations of auxin (Naftaleneacetic AcidANA) - cytokinin (Kinetin-K), with four treatments; and for the different concentrations of two cytokinins 6-Benzylaminopurine and Kinetin, seven treatments and three replicates, under photoperiod conditions. The in vitro plant material used was from the callus, obtained in preestablished trials. The variables evaluated in the differentiation of organogenic structures were: contamination, phenolization, number of de novo shoot formation, number of de novo root formation, number of days to de novo shoot formation, number of days to de novo root formation, length of de novo shoots and length of de novo roots. As shown by the results, contamination in the auxin-cytokinin combinations occurred in treatments T0 and T2 with 20 % and 14 %, respectively; likewise, in the concentrations of two cytokinins, in treatments T1 and T2 with 13 %, followed by treatments T5 and T6 with 7 %. As for phenolization, it was not recorded in any of the treatments. As regards the formation of de novo shoots, the best results were obtained when individual BAP cytokinins were used in T2, with an average of 0.57 formations per application. In de novo root formation, the best result was obtained when using cytokinin KIN individually, at T5 with 93 %.